Integrasi Heuristic Evaluation dan Cognitive Walkthrough sebagai Instrumen Penjaminan Mutu Desain User-Centered pada Sistem Informasi - Andriyan Rizki Jatmiko; Firnanda Achyunda Putra Al Islama; Muhammad Ismail (LPPM Universitas Bina Sarana Informatika, 2026)
User-centered design (UCD) has become essential in enterprise information system development. However, systematic and quantitatively validated usability assurance methods during the design phase remain underutilized. This study proposes and empirically validates a quantitative integration framework combining Heuristic Evaluation (HE) and Cognitive Walkthrough (CW) for enterprise usability assurance. A high-fidelity interactive enterprise dashboard prototype developed in Figma was evaluated by five expert reviewers using Nielsen’s ten heuristics and seven task-based walkthrough scenarios. After normalization and deduplication, the integrated approach identified 68 unique usability issues. HE contributed 42 issues, while CW identified 31 issues, with 39.7% overlapping findings. The proposed integration achieved a 61.9% coverage improvement compared to the best single method. Severity analysis revealed a Mean Severity Index of 2.24 and a Weighted Severity Score of 94 (HE) and 70 (CW), indicating moderate-to-high usability risk. Inter-rater reliability measured using Fleiss’ Kappa yielded κ = 0.78, demonstrating substantial agreement among evaluators. Additionally, the detection efficiency reached 2.47 issues per person-hour, supporting the framework’s practical feasibility. The findings demonstrate that the proposed integration framework enhances usability detection coverage, maintains high evaluation consistency, and provides a cost-effective approach for early-stage enterprise system design assurance.